eiraszero11cu

Answered question

2021-12-31

I am looking for a short proof that
${\int }_{0}^{\mathrm{\infty }}{\left(\frac{\mathrm{sin}x}{x}\right)}^{2}dx=\frac{\pi }{2}$
What do you think?

Answer & Explanation

twineg4

Beginner2022-01-01Added 33 answers

Well, it's not hard to reduce this integral to $f\left(x\right)=max\left\{0,1-|x|\right\}$. It is easy to calculate the Fourier transform
$\stackrel{^}{f}\left(\xi \right)={\int }_{-\mathrm{\infty }}^{\mathrm{\infty }}f\left(x\right){e}^{-ix\xi }={\left(\frac{\mathrm{sin}\left(\frac{\xi }{2}\right)}{\frac{\xi }{2}}\right)}^{2}$
Taking the inverse Fourier transform, we get
${\int }_{-\mathrm{\infty }}^{\mathrm{\infty }}{\left(\frac{\mathrm{sin}\left(\frac{\xi }{2}\right)}{\frac{\xi }{2}}\right)}^{2}{e}^{ix\xi }d\xi =2\pi f\left(x\right)$,
and the result follows.
The second integral can be computed in a similar way. Just take $f\left(x\right)={\chi }_{\begin{array}{cc}-1& 1\end{array}}\left(x\right)$ (the indicator function of the interval $\left[-1,1\right]\right)$

Karen Robbins

Beginner2022-01-02Added 49 answers

${\int }_{0}^{\mathrm{\infty }}\frac{{\mathrm{sin}}^{2}x}{{x}^{2}}dx={\int }_{0}^{\mathrm{\infty }}\frac{\frac{12}{1-\mathrm{cos}2x}}{{x}^{2}}dx$
$={\int }_{0}^{\mathrm{\infty }}\frac{1-\mathrm{cos}x}{{x}^{2}}dx$
$=\frac{1}{2}{\int }_{-\mathrm{\infty }}^{\mathrm{\infty }}\frac{1-\mathrm{cos}x}{{x}^{2}}dx$
$={\frac{12}{\int }}_{-\mathrm{\infty }}^{\mathrm{\infty }}\frac{1-\mathrm{cos}x}{{x}^{2}}dx$
$=\frac{1}{2}{\int }_{-\mathrm{\infty }}^{\mathrm{\infty }}\mathfrak{R}\frac{1-e\left\{ix\right\}}{{x}^{2}}dx$
$=\frac{1}{2}{\int }_{-\mathrm{\infty }}^{\mathrm{\infty }}\mathfrak{R}\frac{1-{e}^{ix}+i\frac{x}{1+{x}^{2}}}{{x}^{2}}dx$
$=\frac{1}{2}\mathfrak{R}{\int }_{-\mathrm{\infty }}^{\mathrm{\infty }}\frac{1-{e}^{ix}+i\frac{x}{1+{x}^{2}}}{{x}^{2}}dx$
Now close the contour in the upper half plane, enclosing the pole at $x=i$ with residue $\frac{1}{2i}$, yielding
${\int }_{0}^{\mathrm{\infty }}\frac{{\mathrm{sin}}^{2}x}{{x}^{2}}dx=\frac{1}{2}\cdot 2\pi \cdot \frac{1}{2i}=\frac{\pi }{2}$

Vasquez

Expert2022-01-09Added 669 answers

From squaring the identity
$\frac{\mathrm{sin}nx}{\mathrm{sin}x}=\frac{{e}^{inx}-{e}^{-inx}}{{e}^{ix}-e-ix}=\sum _{k=0}^{n-1}{e}^{\left(2k-n+1\right)ix}$
and integrating we get
$n\pi ={\int }_{-\pi /2}^{\pi /2}\frac{{\mathrm{sin}}^{2}nx}{{\mathrm{sin}}^{2}x}dx$
Let
${I}_{n}={\int }_{-\pi /2}^{\pi /2}\frac{{\mathrm{sin}}^{2}nx}{n{x}^{2}}dx={\int }_{-n\pi /2}^{n\pi /2}\frac{{\mathrm{sin}}^{2}y}{{y}^{2}}dy$
Then
$\pi -{I}_{n}=\frac{1}{n}{\int }_{-\pi /2}^{\pi /2}{\mathrm{sin}}^{2}nx\left({\mathrm{csc}}^{2}x-{x}^{-2x}\right)dx$
and so
$|\pi -{I}_{n}|\le \frac{1}{n}{\int }_{-\pi /2}^{\pi /2}|{\mathrm{csc}}^{2}x-{x}^{-2}|dx=O\left(1/n\right)$
as $x↦{\mathrm{csc}}^{2}x-{x}^{-2}$ extends to a continuous function on $\left[-\pi /2,\pi /2\right]$. Hence ${I}_{n}\to \pi$ as $n\to \mathrm{\infty }$ and
$\pi ={\int }_{\mathrm{\infty }}^{\mathrm{\infty }}\frac{{\mathrm{sin}}^{2}y}{{y}^{2}}dy$

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?